Annual training load and jumping- and sprinting-characteristic changes during a periodized training plan in a Division I male championship basketball team - Chiang, C.-Y.; Chiang, Y.-C.; Chang, C.-C.; Morrison, M.; Weakley, J. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Optimizing performance while managing training load (TL) is a constant goal in high-performance sport. However, there is limited evidence on how year-long TL variations influence jumping and sprinting characteristics in collegiate basketball. This study aimed to analyze changes in TL and physical performance in a Taiwanese collegiate men`s basketball team during a full year-long season.